1989
DOI: 10.1104/pp.89.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Activities in Tonoplast and Plasmalemma Membranes from Corn Roots

Abstract: Protein kinase and phosphatase activities were studied in plasmalemma and tonoplast membrane fractions from com (Zea mays L.) roots in order to test the hypothesis that the tonoplast H+-ATPase is regulated by intrinsic protein phosphorylation (G Zocchi, SA Rogers, JB Hanson 1983 Plant Sci Lett 31: 215-221), and to facilitate future purification of kinase activities from these membranes. Kinase activity in the plasmalemma was about threefold higher than in the tonoplast, and displayed Michaelis Mententype behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…To address this question, we studied the effect of CaM on the dissipation of ApH after H+-pumping was stopped by inhibiting the H+-ATPase or by depleting the ATP. As shown in Figure 2A (12).…”
Section: Effect Of Ca2+ and Cam On Aph Formationmentioning
confidence: 74%
See 3 more Smart Citations
“…To address this question, we studied the effect of CaM on the dissipation of ApH after H+-pumping was stopped by inhibiting the H+-ATPase or by depleting the ATP. As shown in Figure 2A (12).…”
Section: Effect Of Ca2+ and Cam On Aph Formationmentioning
confidence: 74%
“…These membranes were enriched in tonoplast-type ATPase activity that was inhibited strongly by N03-and less by VO43+, and stimulated by anions and not cations (1,12,16). ATP-dependent formation of ApH across these membrane vesicles, measured by fluorescence quench of quinacrine (1), was abolished by 20 mM N03-, whereas 100 MM V043+ had no effect (US Ladror, RE Zielinski, not shown).…”
Section: Origin Of the Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibiting effect on H+ pumping and ATPase did not appear to be due to a nonspecific action of 2H20 on plasma membrane; NADH-ferricyanide reductase and 1,3-#-glucan synthase, two other plasma membrane activities, were slightly (less than 14%) inhibited by 2H20 (Table IV). Measurements of the ATPase activities present in the tonoplast-enriched fraction (19) and submitochondrial particles showed that they were not, or were very slightly, inhibited by 2H20 (data not shown).…”
Section: Preparation Of Plasma Membrane and Enzymic Activity Measuremmentioning
confidence: 99%